2007
DOI: 10.1002/ebch.206
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane review: Cognitive behavioural therapy for anxiety disorders in children and adolescents

Abstract: BackgroundChildhood and adolescent anxiety disorders are relatively common, occurring in between 5‐18% of all children and adolescents. They are associated with significant morbidity and impairment in social and academic functioning, and when persistent, there is a risk of depression, suicide attempts and substance abuse in adulthood. There is accumulating evidence for the efficacy of cognitive behavioural therapy (CBT), with a number of randomised controlled trials (RCTs) suggesting benefit.ObjectivesTo deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…They cause substantial impairment across a variety of domains of functioning (e.g., academic, social, familial); are highly comorbid with other psychiatric disorders; and often persist into adulthood (Anderson 1994;Biggs et al 2011;Chorpita and Southam-Gerow 2006;Mendlowicz and Stein 2000;Merikangas and Avenevoli 2002;Mychailyszyn et al 2010;Quilty et al 2003). Fortunately, multiple literature reviews have concluded that cognitive behavioral therapy (CBT) is ''probably efficacious'' for childhood anxiety disorders (CADs; defined here as social phobia, generalized anxiety disorder, and separation anxiety disorder 1 ; Chambless and Ollendick 2001;Chorpita et al 2011;James et al 2005Kendall et al 2012Manassis et al 2010;Ollendick and King 1998;Reynolds et al 2012;Seligman and Ollendick 2011;Silverman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They cause substantial impairment across a variety of domains of functioning (e.g., academic, social, familial); are highly comorbid with other psychiatric disorders; and often persist into adulthood (Anderson 1994;Biggs et al 2011;Chorpita and Southam-Gerow 2006;Mendlowicz and Stein 2000;Merikangas and Avenevoli 2002;Mychailyszyn et al 2010;Quilty et al 2003). Fortunately, multiple literature reviews have concluded that cognitive behavioral therapy (CBT) is ''probably efficacious'' for childhood anxiety disorders (CADs; defined here as social phobia, generalized anxiety disorder, and separation anxiety disorder 1 ; Chambless and Ollendick 2001;Chorpita et al 2011;James et al 2005Kendall et al 2012Manassis et al 2010;Ollendick and King 1998;Reynolds et al 2012;Seligman and Ollendick 2011;Silverman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment outcome studies have shown that exposure-based CBT, in both individual and group format, is effective in eliminating anxiety disorders in approximately 50e85% of anxious children (Barrett, Dadds, & Rapee, 1996;Cobham, Dadds, & Spence, 1998;In-Albon & Schneider, 2007;Kendall, 1994;Lyneham & Rapee, 2005;Saavedra et al, 2010;Silverman, Pina, & Viswesvaran, 2008;Waters, Ford, Wharton, & Cobham, 2009) with large scale reviews concluding that about 60% of anxious children will experience significant reductions in anxiety symptoms (James, Soler, & Weatherall, 2007). These rates highlight the need for further research into the underlying mechanisms of anxiety disorders in children and how such mechanisms influence treatment outcomes following exposure-based CBT.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of depression and anxiety in adolescence may mark the development of a mental illness, as up to 75% emerge before the age of 25 [4]. Early intervention is critical to prevent chronic impairment [5], with a number of evidence-based treatments available to prevent and reduce symptoms of anxiety and depression [6][7][8]. However, many adolescents do not seek help for mental health problems from professional services.…”
Section: Introductionmentioning
confidence: 99%